Days Alive and out of Hospital at 30 Days After Curative Gastrectomy for Gastric Adenocarcinoma: Complication-Severity Gradient and Readmission Burden - Adem Ozcan; Gizem Gunes; Ali Bal; Abdulkadir Unsal (Journal of Clinical Medicine, 2026)
Background/Objectives: Days alive and out of the hospital at 30 days (DAOH30) integrates survival, index hospitalization, and readmission. We characterized DAOH30 after gastrectomy, assessed its complication-severity gradient and readmission burden, and explored its association with an index-cancer-excluded Charlson Comorbidity Index (CCI). Methods: This single-center retrospective analysis included adults undergoing R0 total gastrectomy or subtotal distal gastrectomy for non-metastatic gastric adenocarcinoma between January 2020 and April 2026. DAOH30 was derived from the index postoperative length of stay, readmission days, and 30-day mortality. Rank-based tests and median quantile regression were used. Results: Among 123 patients, median DAOH30 was 21 days (interquartile range, 18–22; range, 4–26). No 30-day deaths occurred; eight patients (6.5%) were readmitted. Median DAOH30 decreased from 22 days without complications to 21 days after Clavien–Dindo grade I–II complications and 17 days after grade ≥ III complications (Kruskal–Wallis p < 0.001; one-sided Jonckheere–Terpstra p < 0.001; two-sided permutation sensitivity p < 0.001). After adjustment, grade ≥ III complications were associated with 4.00 fewer median DAOH30 days (bootstrap 95% confidence interval, −7.31 to −2.25; model-based p < 0.001). Readmissions contributed 73 additional inpatient days, with a median decrement of 9.5 days per readmitted patient. No statistically significant independent association was detected between the index-cancer-excluded CCI and DAOH30 (adjusted median difference, −0.17 days per point; bootstrap 95% confidence interval, −1.34 to 0.40; model-based p = 0.640). Conclusions: DAOH30 summarized early hospital burden, but in this no-mortality, low-readmission cohort it was largely determined by index length of stay. Multicenter validation with patient-reported anchoring is warranted.